Marfan syndrome is the main independent predictor of recurrent aortic dissection in patients enrolled in the International Registry of Aortic Dissection (IRAD) - Schoenhoff, Florian S.; Carrel, Thierry P. (Journal of Thoracic Disease, 2016)
In the October 2016 issue of Circulation (1), Isselbacher and colleagues published their observations regarding patients with recurrent aortic dissection enrolled in the International Registry of Aortic Dissection (IRAD).